Effects of different doses of glucose and fructose on central metabolic pathways and intercellular wireless communication networks in humans - Dingqiang Lu; Yujiao Liu; Miao Zhao; Shuai Yuan; Danyang Liu; Xinqian Wang; Yixuan Liu; Yifei Zhang; Ming Li; Yufeng Lü; Guangchang Pang; Ruijuan Ren (Food Science and Human Wellness)
Fructose and glucose are often widely used in food processing and may contribute to many metabolic diseases. To observe the effects of different doses of glucose and fructose on human metabolism and cellular communication, volunteers were given low, medium, and high doses of glucose and fructose. Serum cytokines, glucose, lactate, nicotinamide adenine dinucleotide (NADH) and metabolic enzymes were assayed, and central carbon metabolic pathway networks and cytokine communication networks were constructed. The results showed that the glucose and fructose groups basically maintained the trend of decreasing catabolism and increasing anabolism with increasing dose. Compared with glucose, low-dose fructose decreased catabolism and increased anabolism, significantly enhanced the expression of the inflammatory cytokine interferon-γ (IFN-γ), macrophage-derived chemokine (MDC), induced protein-10 (IP-10), and eotaxin, and significantly reduced the activity of isocitrate dehydrogenase (ICDH) and pyruvate dehydrogenase complexes (PDHC). Both medium and high doses of fructose increase catabolism and anabolism, and there are more cytokines and enzymes with significant changes. Furthermore, multiple cytokines and enzymes show strong relevance to metabolic regulation by altering the transcription and expression of enzymes in central carbon metabolic pathways. Therefore, excessive intake of fructose should be reduced to avoid excessive inflammatory responses, allergic reactions and autoimmune diseases.